Analysis of Mental Workload on Sugar Production Mechanical Workers Using the Nasa-TLX Method - Zidan, Muhammad Faqih; Apriani, Ratna Agil; Basuki, Demas Emirbuwono; Wibowo, Latifah Fitri Nuraida; Mukarim, Rifki Nurul (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2024)
Workload can be defined as the difference between a worker's ability and job demands. Based on observations that have been made, it is known that madukismo sugar companies get an increasing demand value in each season of production, so this causes an increase in the number of working hours that apply to the company, which has the potential to increase their mental work. This study investigated the mechanical mental workload of workers at Madukismo Sugar Company using the NASA-TLX method, a multidimensional assessment tool. The NASA-TLX method is a multidimensional assessment method that can measure the overall mental workload to determine the mental workload felt by each worker. The results indicate a very high mental workload in some operators and suggest the need for operational adjustments. The recommendations are additional manpower and improved ergonomic levels to reduce stress and increase productivity. Keywords: Mental Workload, NASA-TLX, Job Demands